A series of unfortunate events - Snicket, Lemony (HarperCollinsPublishers, 2017)
The events recounted in this four-book box set (which includes The Bad Beginning, The Reptile Room, The Wide Window, and The Miserable Mill) are sure to depress you. If you cannot stomach stories that find misfortune continuously befalling the three charming Baudelaire orphans, I recommend you make another reading selection. The terrible tale of the Baudelaire's bad luck starts with The Bad Beginning, and it all gets worse from there.